Enhancing Human Capital in Malawi : The Role of Maternal and Child Health and Nutrition Services - World Bank (World Bank, Washington, DC, 2021)
Human capital is the combination of knowledge, skills and health that people accumulate throughout their lives, which allows them to realize their potential as productive members of society. The productivity of a country is affected by the quality and availability of maternal and child health services more generally. Simply put, countries which invest heavily in maternal and childhood interventions, together with high-quality nutritional support, are more productive. Recognizing this, the government of Malawi is implementing its ambitious Second Health Sector Strategic Plan (2017-2022) and an aligned National Multi-Sector Nutrition Policy, which promote a range of evidence-based interventions to improve maternal and child health. This policy brief draws on Malawi’s 2018-2019 Harmonised Health Facility Assessment (HHFA) to identify the key health sector service gaps that stand in the way of children growing up healthy and being productive members of their communities and country.